(untitled) (Reflection and Critique Law Magazine, 2022)
The Federal Constitution guarantees immunity from “ICMS” (tax on goods and services) to certain operations. Among these it is worth to highlight the exports. As a rule, operations excluded from ICMS dos not have the right to use the tax previously charged, a benefit supported by the constitutional principle of non-cumulative ICMS credit. However, such provision is not applied to exports that can use the credit from ICMS on other operations that are taxed or transfer it to other people. But the complementary law number 87/96 restricts this benefit when it concerns to goods of use or consumption imposing temporary requirement to its use. The present paper aims to analyses exports operations in the light of non-cumulative principle such as the unconstitutionality of the mentioned law once the use of ICMS credit is ensured by Constitution for exports operations and the Magna Carta does not impose any restriction to the use of the benefit.